Organic Synthesis A Nascent Relook - Parameshwarappa Nandeshwarappa, Belakatte (IntechOpen, 2020)
The book 'Organic Synthesis - A Nascent Relook' is a compendium of the recent progress in all aspects of organic chemistry including bioorganic chemistry, organo-metallic chemistry, asymmetric synthesis, heterocyclic chemistry, natural product chemistry, catalytic, green chemistry and medicinal chemistry, polymer chemistry, as well as analytical methods in organic chemistry. The book presents the latest developments in these fields. The chapters are written by chosen experts who are internationally known for their eminent research contributions. Organic synthesis is the complete chemical synthesis of a target molecule. In this book, special emphasis is given to the synthesis of various bioactive heterocycles. Careful selection of various topics in this book will serve the rightful purpose for the chemistry community and the industrial houses at all levels.